Refleksje nad zastosowaniem korczakowskich metod partycypacyjnej pracy z dziećmi w obozach dla uchodźców - Urszula Markowska-Manista; Dominika Zakrzewska-Olędzka (Problemy Wczesnej Edukacji)
The aim of the article is to outline the specifics of places and spaces – refugee camps and centers, where children constitute the majority. Through reference to activities implemented there and oriented towards children, we discuss their problematic character connected with e.g. the absence of participatory, rights-based approach (art. 12 CRC) that serves children’s emancipation and equality. In the second part of the article, we propose the implementation of Janusz Korczak’s methods – solutions for participatory work with children (“underprivileged” groups), which seem both timeless and universal. An ethical and contextual adaptation or inspiration based on Korczak’s methods in work designed for backgrounds connected with children remaining in closed and semi-closed systems, provides a chance for children’s basic participation in decision-making in matters that concern their lives. At the same time, it is an opportunity to learn children’s opinions and an expression of respect for the child as a per-son who functions here and now, in the place and space of his or her temporary stay – a refugee camp, where an international protection system for children and adults is far from effective.